A Comparison of Behavioral and Psychological Symptoms of Dementia (BPSD) and BPSD Sub-Syndromes in Early-Onset and Late-Onset Alzheimer's Disease. - Altomari, Natalia; Bruno, Francesco; Laganà, Valentina; Smirne, Nicoletta; Colao, Rosanna; Curcio, Sabrina; Di Lorenzo, Raffaele; Frangipane, Francesca; Maletta, Raffaele; Puccio, Gianfranco; Bruni, Amalia Cecilia (J Alzheimers Dis, 2022)
BACKGROUND: Behavioral and psychological symptoms of dementia (BPSD) have a large impact on the quality of life of patients with Alzheimer's disease (AD). Few studies have compared BPSD between early-onset (EOAD) and late-onset (LOAD) patients, finding conflicting results. OBJECTIVE: The aims of this study were to: 1) characterize the presence, overall prevalence, and time of occurrence of BPSD in EOAD versus LOAD; 2) estimate the prevalence over time and severity of each BPSD in EOAD versus LOAD in three stages: pre-T0 (before the onset of the disease), T0 (from onset to 5 years), and T1 (from 5 years onwards); 3) track the manifestation of BPSD sub-syndromes (i.e., hyperactivity, psychosis, affective, and apathy) in EOAD versus LOAD at T0 and T1. METHODS: The sample includes 1,538 LOAD and 387 EOAD diagnosed from 1996 to 2018. Comprehensive assessment batteries, including the Neuropsychiatric Inventory (NPI), were administered at the first medical assessment and at different follow-up period. RESULTS: The overall prevalence for the most of BPSD was significantly higher in EOAD compared to LOAD whereas most BPSD appeared significantly later in EOAD patients. Between the two groups, from pre-T0 to T1 we recorded a different pattern of BPSD prevalence over time as well as for BPSD sub-syndromes at T0 and T1. Results on severity of BPSD did not show significant differences. CONCLUSION: EOAD and LOAD represent two different forms of a single entity not only from a neuropathological, cognitive, and functional level but also from a psychiatric point of view.
Keywords: Affective Symptoms; Age of Onset; Aged; Aged, 80 and over; Alzheimer Disease; Apathy; Behavioral Symptoms; Dementia; Female; Humans; Italy; Male; Middle Aged; Neuropsychological Tests; Psychiatric Status Rating Scales; Psychomotor Agitation; Psychotic Disorders; Severity of Illness Index

Frequency of Cardiovascular Genetic Risk Factors in a Calabrian Population and Their Effects on Dementia. - Maletta, Raffaele; Smirne, Nicoletta; Bernardi, Livia; Anfossi, Maria; Gallo, Maura; Conidi, Maria Elena; Colao, Rosanna; Puccio, Gianfranco; Curcio, Sabrina A M; Laganà, Valentina; Frangipane, Francesca; Cupidi, Chiara; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Several genetic variants playing a key role in cholesterol levels, blood pressure, and vascular dysfunction influence the risk of Alzheimer's disease (AD) and vascular dementia (VaD). The many meta-analysis studies carried out on large numbers of samples in different populations have not provided clear results to date, because a trans-ethnic shift of risk genotypes in different populations is often observed. OBJECTIVES: To determine genotypes allele frequencies of the polymorphisms most frequently identified to be correlated with cardio-cerebrovascular disease and AD in a Southern Italy population and to investigate their possible association with dementia. METHODS: The genotype and allele frequencies of 13 cardio-cerebrovascular risk polymorphisms were assessed and their possible association with dementia was investigated in a case-control study, including 221 consecutive unrelated subjects diagnosed with dementia (120 subjects affected by AD, 55 by frontotemporal dementia, and 33 by vascular dementia) and 218 matched controls of Calabrian origin. RESULTS: Carriers of at least one APOEɛ4 allele resulted to be at higher risk of AD [OR(95% CI) = 2.721(1.477-5.011)] and VaD [OR(95% CI) = 6.205(2.356-16.342)] compared to non-carriers. Individuals with the IV genotype of the CETP polymorphism were more likely to have AD [OR(95% CI) = 2.427(1.364-4.319)] and VaD [OR(95% CI) = 3.649(1.455-9.152)] compared to subjects with the II-VV genotypes. CONCLUSION: CETP I405V polymorphism is likely a risk factor for AD and VaD in our cohort, independent of APOEɛ4 status. Unmodifiable genetic risk factors should be taken into account to promote a healthy lifestyle to prevent dementia.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoprotein E4; Case-Control Studies; Cholesterol Ester Transfer Proteins; Cohort Studies; Dementia, Vascular; Female; Frontotemporal Dementia; Gene Frequency; Humans; Italy; Male; Middle Aged; Polymorphism, Genetic; Risk Factors

Prevalence of Delirium in a Population of Elderly Outpatients with Dementia: A Retrospective Study. - Addesi, Desirée; Maio, Raffaele; Smirne, Nicoletta; Laganà, Valentina; Altomari, Natalia; Puccio, Gianfranco; Colao, Rosanna; Cupidi, Chiara; Perticone, Francesco; Bruni, Amalia Cecilia (J Alzheimers Dis, 2018)
BACKGROUND: Delirium is a multifactorial geriatric syndrome and often occurs in patients with cognitive impairment. It also remains under-recognized, specifically in elderly outpatients, because signs of delirium might overlap with symptoms of dementia. OBJECTIVE: The aim of the present study is to retrospectively apply the chart-based delirium instrument on a cohort of elderly outpatients with dementia, to assess prevalence and features of delirium in this population. METHODS: We randomly selected 650 medical records of outpatients referred to the "Neurogenetic Regional Centre" (CRN) of Lamezia Terme. Each evaluation included demographics, medical history, drugs, type and severity of dementia, and cognitive and functional status. Delirium was identified by the application of the chart-based delirium instrument. RESULTS: The prevalence of delirium was 13.3%. The study population was divided, according to the presence of delirium, into two subgroups. Compared to the no delirium group, the delirium group was significantly older and had greater cognitive impairment with lower MMSE scores both at baseline and at the end of the follow up. They also had a significant lower score on the ADL and IADL. In this group, a higher intake of antihypertensive and antipsychotic drugs, together with a lower intake of cholinesterase inhibitors and memantine, was observed. CONCLUSIONS: In this study, the chart-based delirium instrument was applied to an outpatient population affected by dementia and followed for a long time. Our data confirm the importance that age and frailty play on the genesis of delirium and suggest attention should be paid to the pharmacological treatment of these patients.
Keywords: Aged; Aged, 80 and over; Antipsychotic Agents; Cohort Studies; Delirium; Dementia; Female; Geriatric Assessment; Humans; Male; Outpatients; Prevalence; Severity of Illness Index

Effects of Multiple Genetic Loci on Age at Onset in Frontotemporal Dementia. - Ferrari, Raffaele; Grassi, Mario; Graziano, Francesca; Palluzzi, Fernando; Archetti, Silvana; Bonomi, Elisa; Bruni, Amalia C; Maletta, Raffaele G; Bernardi, Livia; Cupidi, Chiara; Colao, Rosanna; Rainero, Innocenzo; et al. (J Alzheimers Dis, 2017)
In frontotemporal dementia (FTD), age at disease onset (AAO) is unpredictable in both early and late-onset cases; AAO variability is found even in autosomal dominant FTD. The present study was aimed at identifying genetic modifiers modulating AAO in a large cohort of Italian FTD patients. We conducted an association analysis on 411 FTD patients, belonging to 7 Italian Centers, and for whom AAO was available. Population structure was evaluated by principal component analysis to infer continuous axes of genetic variation, and single linear regression models were applied. A genetic score (GS) was calculated on the basis of suggestive single nucleotide polymorphisms (SNPs) found by association analyses. GS showed genome-wide significant slope decrease by -3.86 (95% CI: -4.64 to -3.07, p < 2×10-16) per standard deviation of the GS for 6 SNPs mapping to genes involved in neuronal development and signaling, axonal myelinization, and glutamatergic/GABA neurotransmission. An increase of the GS was associated with a decrease of the AAO. Our data indicate that there is indeed a genetic component that underpins and modulates up to 14.5% of variability of AAO in Italian FTD. Future studies on genetic modifiers in FTD are warranted.

Role of Niemann-Pick Type C Disease Mutations in Dementia. - Cupidi, Chiara; Frangipane, Francesca; Gallo, Maura; Clodomiro, Alessandra; Colao, Rosanna; Bernardi, Livia; Anfossi, Maria; Conidi, Maria Elena; Vasso, Franca; Curcio, Sabrina Anna Maria; Mirabelli, Maria; Smirne, Nicoletta; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Several neurological and systemic diseases can cause dementia, beyond Alzheimer's disease. Rare genetic causes are often responsible for dementia with atypical features. Recently, mutations causative for Niemann-Pick type C disease (NPC) have also been implicated in neurodegenerative diseases. NPC is an autosomal recessive lipid storage disorder caused by mutations in NPC1 and NPC2 genes. In adults, clinical presentation mimicking other neurodegenerative diseases makes diagnosis difficult. Recent evidence suggests that heterozygous mutations in NPC genes may take on etiological significance. OBJECTIVE: To investigate the presence of NPC1 and NPC2 mutations in adults affected by neurodegenerative dementia plus. METHODS: We performed a genetic screening on 50 patients using a wide clinical and biochemical approach to characterize the phenotype of mutated patients. RESULTS: Sequencing analysis revealed four different and known heterozygous mutations in NPC1 and NPC2 genes. Patient 1 carried the p. F284LfsX26 in NPC1 and was affected by progressive supranuclear palsy-like syndrome. The remaining three patients showed a corticobasal syndrome and harbored the c.441+1G>A variant of NPC2 (patient 2), the missense p.N222 S mutation associated with the c.1947+8G>C variant in the splice region of intron 12 in NPC1 (patient 3), and the p.V30M mutation in NPC2 (patient 4), respectively. Filipin staining was abnormal in patients 1 and 2. mRNA analysis revealed an altered splicing of the NPC2 gene in patient 2. CONCLUSIONS: Heterozygous mutations of NPC1 and NPC2 genes could contribute to dementia plus, at least in a subset of patients. We highlight the occurrence of NPC1 and NPC2 heterozygous variants in dementia-plus as pathological event.

Genetic Counseling and Testing for Alzheimer's Disease and Frontotemporal Lobar Degeneration: An Italian Consensus Protocol. - Bocchetta, Martina; Mega, Anna; Bernardi, Livia; Di Maria, Emilio; Benussi, Luisa; Binetti, Giuliano; Borroni, Barbara; Colao, Rosanna; Di Fede, Giuseppe; Fostinelli, Silvia; Galimberti, Daniela; Gennarelli, Massimo; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Genetic testing of familial Alzheimer's disease (AD) and frontotemporal lobar degeneration (FTLD) is attracting interest thanks to innovative primary prevention clinical trials and increased request for information by at-risk individuals. However, ethical, social, and psychological implications are paramount and genetic testing must be supported by structured genetic counseling. In Italy, practice parameters and guidelines for genetic counseling in dementia are not available. OBJECTIVE: To develop a nationally harmonized protocol for genetic counseling and testing of familial AD and FTLD. METHODS: Activities were carried out in the context of the Italian Dominantly Inherited Alzheimer's and Frontotemporal Network (IT-DIAfN) project, a national network of centers of excellence with expertise in managing patients with familial AD and FTLD. A survey of the literature on genetic counseling protocols and guidelines was conducted. Local protocols for genetic counseling were surveyed. Differences and commonalities among protocols were identified and discussed among project partners. Consensus was reached following implicit aggregation methods. RESULTS: Consensus was reached on a protocol for patients with clinically diagnosed familial AD or FTLD and a distinct protocol for their at-risk relatives. Genetic counseling should be provided by a multidisciplinary team including a geneticist, a neurologist/geriatrician, and a psychologist/psychiatrist, according to the following schedule: (i) initial consultation with tailored information on the genetics of the dementias; (ii) clinical, psychological, and cognitive assessment; if deemed appropriate (iii) genetic testing following a structured decision tree for gene mutation search; (iv) genetic testing result disclosure; (v) psychological support follow-up. CONCLUSION: This genetic counseling protocol provides Italian centers with a line of shared practice for dealing with the requests for genetic testing for familial AD and FTLD from patients and at-risk relatives, who may also be eligible participants for novel prevention clinical trials.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Consensus; Female; Follow-Up Studies; Frontotemporal Lobar Degeneration; Genetic Counseling; Genetic Testing; Humans; Italy; Male; Peptide Fragments; Psychiatric Status Rating Scales

The Genetic Variability of UCP4 Affects the Individual Susceptibility to Late-Onset Alzheimer's Disease and Modifies the Disease's Risk in APOE-ɛ4 Carriers. - Montesanto, Alberto; Crocco, Paolina; Anfossi, Maria; Smirne, Nicoletta; Puccio, Gianfranco; Colao, Rosanna; Maletta, Raffaele; Passarino, Giuseppe; Bruni, Amalia C; Rose, Giuseppina (J Alzheimers Dis, 2016)
Uncoupling proteins (UCPs) are a group of five mitochondrial inner membrane transporters with a tissue specific expression that uncouple biofuel oxidation from ATP synthesis and function as regulators of energy homeostasis and antioxidants. Previous data suggested that neuronal UCPs (UCP2, UCP4, and UCP5) can directly influence synaptic plasticity, neurotransmission, and neurodegenerative processes, and have a crucial role in the function and protection of the central nervous system. In fact, it has been observed that the expression of neuronal UCPs significantly decreases in Alzheimer's disease (AD) patients. Here we analyzed the variability of UCP2, -3, -4, and 5 genes in sporadic and familial cases (n = 465) of late-onset AD (LOAD) with respect to healthy controls (n = 442). We showed that a genetic variant in the human UCP4, rs9472817, not only significantly affects the individual susceptibility to LOAD, but also modulates the effect of APOE-ɛ4 on AD risk. In fact, rs9472817-C allele was significantly more frequent in both groups of patients with respect to the control group (p = 6.934*10-4 for familial and p = 1.033*10-3 for sporadic cases). In addition, gene-gene interaction analysis revealed that the effect of APOE-ɛ4 allele on LOAD risk was doubled in homozygote CC subjects; conversely, the risk conferred by the APOE-ɛ4 allele was annulled in subjects with two copies of the G allele. Our findings are further evidence that the efficiency in mitochondrial energy metabolism and oxidative stress are important factors in AD pathogenesis.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoprotein E4; Female; Genetic Association Studies; Genotype; Humans; Male; Mental Status Schedule; Mitochondrial Uncoupling Proteins; Neuroimaging; Polymorphism, Single Nucleotide